Olivia Sharp : The Princess of the Fillmore Street School - Sharmat, Marjorie Weinman; Sharmat, Mitchell; Brunkus, Denise (New York : Yearling, 2005)
Perfect Desiree seeks the help of wealthy problem solver, Olivia Sharp in becoming princess of the school.
"A Yearling Book."
2.0.
006-009.
Keywords: Schools -- Fiction; Schools -- Fiction